2015
DOI: 10.1002/biot.201500028
|View full text |Cite
|
Sign up to set email alerts
|

Post‐harvest light treatment increases expression levels of recombinant proteins in transformed plastids of potato tubers

Abstract: Plastid genetic engineering represents an attractive system for the production of foreign proteins in plants. Although high expression levels can be achieved in leaf chloroplasts, the results for non-photosynthetic plastids are generally discouraging. Here, we report the expression of two thioredoxin genes (trx f and trx m) from the potato plastid genome to study transgene expression in amyloplasts. As expected, the highest transgene expression was detected in the leaf (up to 4.2% of TSP). The Trx protein cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Differently from leaf chloroplasts where high protein expression level can be achieved, the levels of recombinant proteins expressed in non‐photosynthetic plastids are generally rather low. Larraya and colleagues [21] report the results of expressing two thioredoxin genes from the potato plastid genome to study transgene expression in amyloplasts. It was shown that a simple postharvest light treatment of tubers induced up to 55 times higher accumulation of the recombinant protein in just seven to ten days.…”
mentioning
confidence: 99%
“…Differently from leaf chloroplasts where high protein expression level can be achieved, the levels of recombinant proteins expressed in non‐photosynthetic plastids are generally rather low. Larraya and colleagues [21] report the results of expressing two thioredoxin genes from the potato plastid genome to study transgene expression in amyloplasts. It was shown that a simple postharvest light treatment of tubers induced up to 55 times higher accumulation of the recombinant protein in just seven to ten days.…”
mentioning
confidence: 99%